Comunidade Sahu-Apé : produção artesanal e os desdobramentos sociais - Medeiros, Andressa Maria Machado (2019)
This research work had the following theme: Sahu-Apé Community: handicrafts and their social unfolding, and the general objective established was the understanding of how social relations happen from the handicraft production process and the commercialization of handcrafted pieces produced by this social group and what is the impact of this production in these peoples lives. Analyzing the extraordinary potential of handicraft production in the community, it was understood that this activity has the direct participation of women, in the person of tuxaua Baku, in the making and marketing of the pieces made by the others in the village, while men have the responsibility of collecting the material directly into the forest at the time of hunting, fishing and other activities near the village. The methodologies that underpinned and helped in the investigative process were field research, aided by ethnographic study, treated within the qualitative approach, and its assistive tools were observation, interview, notes and records in photographs, audios. and filming. The theoretical support that contributed to this legacy were Torres and Santos (2011), Santos (2015), Barros (2015), Paiva (2016), Prodonov (2013), Oliveira (2011), among others. Above all, it is necessary to understand the handicrafts as a social practice, since it is first and foremost practiced by people who seek alternatives to support the family, as well as stimulate concentration, creativity and the development of other skills, serving as a means of occupation, leisure and integration. In addition, crafts and tourism cause changes for the tourist and the resident population. The research also revealed that the dynamics that move the community is indispensable in social life and expresses a relevant tool to understand the interrelations and manifestations of work in this particular area.